2019
DOI: 10.1186/s13287-019-1257-2
|View full text |Cite
|
Sign up to set email alerts
|

Distal airway stem cells ameliorate bleomycin-induced pulmonary fibrosis in mice

Abstract: Background Idiopathic pulmonary fibrosis is characterized by loss of lung epithelial cells and inexorable progression of fibrosis with no effective and approved treatments. The distal airway stem/progenitor cells (DASCs) have been shown to have potent regenerative capacity after lung injury. In this work, we aimed to define the role of mouse DASCs (mDASCs) in response to bleomycin-induced lung fibrosis in mice. Methods The mDASCs were isolated, expanded in vitro, and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 33 publications
3
27
1
Order By: Relevance
“…For instance, intratracheally instillation of bleomycin will lead to an acute lung injury response or even death during the early stage (Adamson and Bowden, 1974), while IPF often has an insidious onset and does not have such a phase of acute lung injury before lung fibrosis. In this animal model of lung fibrosis, many non-AEC2 progenitor/stem cells have been found to be activated and help restore the impaired alveolar epithelium (Chapman et al, 2011;Vaughan et al, 2015;Guha et al, 2017;Salwig et al, 2019;Shi et al, 2019). This may account for the self-resolution of bleomycin-induced lung fibrosis.…”
Section: Non-aec2 Progenitor/stem Cells May Not Activate Upon Mild Inmentioning
confidence: 96%
See 2 more Smart Citations
“…For instance, intratracheally instillation of bleomycin will lead to an acute lung injury response or even death during the early stage (Adamson and Bowden, 1974), while IPF often has an insidious onset and does not have such a phase of acute lung injury before lung fibrosis. In this animal model of lung fibrosis, many non-AEC2 progenitor/stem cells have been found to be activated and help restore the impaired alveolar epithelium (Chapman et al, 2011;Vaughan et al, 2015;Guha et al, 2017;Salwig et al, 2019;Shi et al, 2019). This may account for the self-resolution of bleomycin-induced lung fibrosis.…”
Section: Non-aec2 Progenitor/stem Cells May Not Activate Upon Mild Inmentioning
confidence: 96%
“…Vaughan et al (2015) discovered a small proportion of Krt5-lineage labeled cells in the injured mouse alveolar epithelium, indicating that the preexisting Krt5 + cells from bronchioles might migrate to the alveolar region during wound repair. Several studies have identified distal airway stem/progenitor cells referred to as DASCs, which expressed p63 and Krt5, and could regenerate the bronchiolar and alveolar epithelium after influenza or bleomycin injury in mice (Kumar et al, 2011;Zuo et al, 2015;Shi et al, 2019). Other than the preexisting p63 + /Krt5 + cells, there is a rare subpopulation of progenitor cells in mouse distal airway named as lineage-negative epithelial stem/progenitors (LNEPs) marked by CC10 − β4 + CD200 + CD14 + (Vaughan et al, 2015).…”
Section: Potential Role Of Other Epithelial Progenitor/stem Cells In Ipfmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes modulation of endogenous lung epithelial progenitor cells and their environment with small and large molecules, as well as exogenous delivery of stromal cells or lung epithelial progenitor cells or their secreted products to promote regeneration (136). These approaches have shown promise in vitro and in preclinical in vivo models (10,(137)(138)(139)(140) and there are clinical trials of compounds targeting proteins expressed by epithelial cells which have reached Phase II (NCT03832946, galectin-1 and -3 inhibitor GB0139) and III (NCT03711162 and NCT03733444, autotaxin antagonist GLPG1690), albeit targeting of the epithelium was not part of the initial rationale for the implementation of these compounds (141)(142)(143)(144). Autotaxin is known to convert LPC to LPA, which can then elicit pleiotropic effects on numerous cell types including fibroblasts, endothelial cells and epithelial cells (145).…”
Section: Repairing the Damaged Lung Epithelium -The Future Of Ipf Therapeutics?mentioning
confidence: 99%
“…While early trials focused on inhibiting inflammatory processes or modulation of aberrant fibroblast behaviour, recent work has indicated that the distal epithelium is the site of initial injury in pulmonary fibrosis and that modulation of aberrant distal epithelial cell behaviour is sufficient to slow or reverse fibrosis in animal models (9)(10)(11). Additionally, increased epithelial-associated biomarkers identified in the serum of IPF patients was shown to correlate with disease severity bronchioles.…”
Section: Introductionmentioning
confidence: 99%